Innovation in Non-formal Education in Indonesia - Bahri, Efri Syamsul; Aslam, Mohd Mizan Mohammad; Hermawan, Yudan (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2024)
Non-formal education has a strategic role in improving the quality of Indonesia's human resources. One effort to maximize the strategic role of non-formal education is to innovate non-formal education. This research aims to identify innovations in non-formal education in Indonesia. This research uses a qualitative, descriptive approach and literature study. Research data comes from journal articles related to non-formal education innovation from the Google Scholar database. The research results show that non-formal education innovation has been carried out in nine dimensions: social innovation, non-formal education supervision, institutional communication, the strategy of adversity quotient, standard operational procedures, methods, learning media, programs, and learning innovation. Therefore, the government needs to support the development of non-formal education innovations to optimize its strategic role in developing human resources in Indonesia. Apart from that, non-formal education entities need to increase collaboration with their strategic stakeholders.